ANALYSIS OF KNOWLEDGE ON VIRAL HEPATITIS B, C, AND D AND VACCINATION STATUS FOR HEPATITIS B AMONG SCHOOL STUDENTS IN A MUNICIPALITY OF THE STATE OF AMAZONAS, BRAZIL - Alves, José Raimundo Oliveira; da Silva, Beatriz da Paixão Ferreira; da Conceição, Bernardo Farias; de Brito, Dickson Ciro Nascimento; Nunes, Heloisa Marceliano; Sarmento, Vania Pinto; Malheiros, Andreza Pinheiro; de Oliveira, Candida Maria Abrahão (Seven Editora, 2026)
Viral hepatitis, characterized by inflammation of the liver, being best known from types A to E, with fecal-oral, parenteral, vertical, or sexual transmission, is prevalent worldwide. This study aimed to analyze the level of knowledge regarding viral hepatitis and the vaccination status for hepatitis B among students in the municipality of Boca do Acre, Amazonas, Brazil. Sociodemographic information was collected from the participants of a main project. Regarding knowledge of the hepatitis B vaccine, 67.8% claimed to know about vaccines, 77.4% had heard of it, 37.1% did not know about the vaccine and its prevention methods, and 56.5% knew little; regarding possession of a vaccination card, only 8.0% stated having one, and 77.4% did not have the document. Furthermore, 9.8% did not know where it was, and 4.8% had lost it; when asked if three doses hindered the vaccination schedule, 82.3% answered no, and regarding the reasons for not being vaccinated, 29.0% associated it with a lack of knowledge, 1.6% with the difficulty of finding the vaccine, 6.5% with fear, and 14.5% with a lack of interest, however, the majority (48.4%) did not respond. The results of the serological tests HBsAg, anti-HBs, and total anti-HBc were evaluated; a total of 62 students participated, 53.2% of whom were female, with a mean age of 18.9 years and a median of 18 years. Among 6 individuals who participated in the project, it was identified that 66.6% (2/3) had isolated anti-HBs, with 33.3% (1/3) being susceptible. These results demonstrated the need to improve health education strategies, highlighting that raising student awareness about prevention is of fundamental importance as a measure to avoid the transmission of hepatitis virus infections.